Leadership and innovation under decentralization: A case study of selected local governments in the Philippines - Joseph J. Capuno (University of the Philippines, School of Economics (UPSE), 2010)
This study investigates the importance of leadership as a driver of local government innovations. Based on a survey of 209 innovations introduced in selected 48 local governments in the Philippines during the period June 2004-June 2008, the observable qualities and possible incentives of incumbent mayors are linked empirically with their reported number of innovations. The Poisson regression results show that the statistically relevant incumbent's characteristics are age, educational attainment, and experience in the public sector, re-election status and terms in office, controlling for other factors. Also, the fiscal capacity of the local government and the poverty status of the local population are found statistically significant. However, all these factors vary in relative importance across types of innovations. Several policy inputs are suggested to hone the leadership qualities of incumbent mayors for greater adoption of innovations.
Keywords: 330; Incumbent leaders; local government innovations; Philippines; Kommunalverwaltung; Performance-Messung; Philippinen